A method for isolating and culturing placental cells from failed early equine pregnancies. (February 2016) - Rose, B.V.; Cabrera-Sharp, V.; Firth, M.J.; Barrelet, F.E.; Bate, S.; Cameron, I.J.; Crabtree, J.R.; Crowhurst, J.; McGladdery, A.J.; Neal, H.; Pynn, J.; Pynn, O.D.; et al.
Abstract: Early pregnancy loss occurs in 6–10% of equine pregnancies making it the main cause of reproductive wastage. Despite this, reasons for the losses are known in only 16% of cases. Lack of viable conceptus material has inhibited investigations of many potential genetic and pathological causes. We present a method for isolating and culturing placental cells from failed early equine pregnancies. Trophoblast cells from 18/30 (60%) failed equine pregnancies of gestational ages 14–65 days were successfully cultured in three different media, with the greatest growth achieved for cells cultured in AmnioChrome™ Plus. Genomic DNA of a suitable quality for molecular assays was also isolated from 29/30 of these cases. This method will enable future investigations determining pathologies causing EPL. Highlights: Causes of early pregnancy loss in most mammalian species are poorly understood. Investigations are limited due to insufficient methods to isolate failed conceptuses. Conceptuses from 30 failed equine pregnancies were successfully isolated. Viable trophoblast cells were obtained from 60% of early equine conceptuses. Material will assist in future studies that aim to diagnose causes of early pregnancy failure.